TRENDS IN CONTINUING EDUCATION OF TEACHERS IN EUROPEAN EDUCATION SYSTEMS - Kaminska, Malgozhata (The Modern Higher Education Review, 2019)
Continuing education of teachers is one of the most important challenges in the educational policy of the European Union. Primary education and professional development of teachers are considered as strategic factors in the achievement of educational indicators in the 2020 perspective. The article presents the main concepts that characterize continuous education on the background of the concept of continuous education. The provisions on education and professional development of teachers in European educational systems have been analyzed on the basis of research reports, strategies and communications from the Council and the European Commission. There is a growing awareness and sense that improving the quality of general and vocational education cannot take place without taking into account changes in teacher education and training. The level of professional qualifications of teachers is quite high, but initiatives are needed to improve teachers’ professional competences, especially in the area of pedagogical and practical education. The challenge remains to work towards the professional integration of young teachers and – as a result – to limit the outflow of teachers from the profession. This is closely related to the promotion of solutions that will help teachers develop their competence potential and gain new experiences through various forms of professional development. This also applies to non-formal learning and recognition of its effects.